Scopping the Dispute Submitted Before Indonesia Arbitration - I Gusti Agung Ayu Gita Pritayanti Dinar; I Nyoman Bagiastra; I Nyoman Gede Sugiartha (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
The problem of equating the concepts of dispute and default results as legal practitioners tending to assume that every case with an arbitration clause is a dispute that must be examined at an arbitration institution even though the case is not necessarily a dispute because cases, disputes and default have different concepts, nature and causes. According to international instrument, arbitration clause is mandatory for cases that submitted to the arbitration. It shall have clearly regulated under agreement of the parties to the dispute. Thus if there a dispute when implementing their agreement then the settlement brought before arbitration. Unfortunately in the reality is different. This research is used normative legal research methods with approaches: (1) Analitical and Conceptual Approach, and (2) The Statue Approach. The result of this research is between arbitration institutions and general justice must implimentated in harmony and must contribute to each other in creating justice, certainty and benefit of the law in carrying out their duties. Only with this harmony will creating a suitability of judicial competence which is fair to all parties. Regulation regarding the definition of arbitration dispute should be clearly and explicitly stipulated in the general provisions of the Arbitration Law and Alternative Dispute Resolution so that all parties may understanding to and the justice, legal certainty in determining in related cases of the competence of arbitration can be achieved.